มาตรการทางกฎหมายในการฟื้นฟูพื้นที่ทำเหมืองแร่ - ธวัชชัย เทพรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
This research intends to examine legal measures to force reclamation of spoiled mines by analysing the operation mines on land. From the study, it has found that after completing of the mine, most of the concessionaires have neglected to reclaim the mine-spoiled area. This is due to the inadequacy and ineffectiveness of law enforcement. This research proposes an amendment to the law, law enforcement and the authorization of law. The concessionaire must be fully responsible for the said reclamation as well as set up plan to form the direction of measures and bear all the expenses. Those who do not comply with the regulations will not obtain future concessions. There should be a law to enforce the bank or financial guarantor to assure the reclamation. Standardized methods to deal with wastewater should be set up more proper. The authority of the Minister of Industry regarding the concessionaire to release wastewater more than allowed into public waterways should be abolished. The concessionaire must also be responsible to restore environment endangered by toxic minerals and make the directors or managers of such juristic person be joint liability. In implementing and enforcing the law, the Department of Mineral Resources and the Department of Forestry should inspect and order the concessionaire to restore land that was mined according to law and regulations and restore land that the concessionaire did not comply with the regulations by making the concessionaire responsible for the expenses or use the money that collect from the Department of Forestry to plant trees. The Department of Mineral Resources should speed up the inspection of land reclamation by setting out responsibilities of Municipalities and Provincial Administration Organizations. The Department of Pollution Control should set standards to control the toxic waste from the point sources pollution so that Department can inspect and solve the problems. For the role of the people, laws should be issued for citizen suit in order to preserve the environment and for public hearings to prepare the environmental impact assessment.